PEDAGOGICAL FACTORS OF EFL STUDENT'S FORMATION OF WRITING COMPETENCE IN ENGLISH (American Journal of Interdisciplinary Research and Development, 2023)
Learning to write in English is an important part of the English language learning process for EFL students in their education and development. Writing competence can be defined as the ability to produce coherent and grammatically correct written texts in English. As students are expected to produce university-level written work in English, it is essential that they develop good writing competence. In this blog article, we will be discussing the pedagogical factors that influence the formation of writing competence in EFL students at the university level and how they can be used to help improve a student's written ability.